1999
DOI: 10.1083/jcb.146.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Dynein Is Required for the Nuclear Attachment and Migration of Centrosomes during Mitosis inDrosophila

Abstract: Cytoplasmic dynein is a multisubunit minus-end–directed microtubule motor that serves multiple cellular functions. Genetic studies in Drosophila and mouse have demonstrated that dynein function is essential in metazoan organisms. However, whether the essential function of dynein reflects a mitotic requirement, and what specific mitotic tasks require dynein remains controversial. Drosophila is an excellent genetic system in which to analyze dynein function in mitosis, providing excellent cytology in embryonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
192
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(210 citation statements)
references
References 54 publications
17
192
0
1
Order By: Relevance
“…Although we are aware of the caveats, as well as the strengths, of antibody microinjection experiments (Scholey, 1998), we consider it likely that the antibodies used in this study strongly and specifically inhibit the activities of dynein and KLP61F for the following reasons. First, the microinjection of our anti-DHC or anti-KLP61F antibodies produced effects on spindle pole positioning that are similar to those reported in KLP61F (Heck et al, 1993) and dynein (Robinson et al, 1999) mutants. Second, in the case of dynein, two different inhibitors, anti-DHC and p50 dynamitin, produced strikingly similar results.…”
Section: Experimental Rationalesupporting
confidence: 49%
See 3 more Smart Citations
“…Although we are aware of the caveats, as well as the strengths, of antibody microinjection experiments (Scholey, 1998), we consider it likely that the antibodies used in this study strongly and specifically inhibit the activities of dynein and KLP61F for the following reasons. First, the microinjection of our anti-DHC or anti-KLP61F antibodies produced effects on spindle pole positioning that are similar to those reported in KLP61F (Heck et al, 1993) and dynein (Robinson et al, 1999) mutants. Second, in the case of dynein, two different inhibitors, anti-DHC and p50 dynamitin, produced strikingly similar results.…”
Section: Experimental Rationalesupporting
confidence: 49%
“…In the first of these, it was shown that KLP61F and Ncd generate antagonistic forces to position mitotic spindle poles after NEB (Sharp et al, 1999b). More recently, it was shown that hypomorphic mutations in the dynein heavy chain reduced the extent of spindle pole separation during interphase-prophase in this system (Robinson et al, 1999). Although the roles of dynein, KLP61F, and Ncd are also reported here, the important novel feature of our work is to show how the activities of these motors are organized into an ordered pathway for spindle assembly and function.…”
Section: Relationship Of Our Results To Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments with cytochalasin D indicated that actin caps are essential for maintaining an even nuclear spacing in the syncytium and for holding nuclei at the cortex (Sullivan et al, 1993;Foe et al, 2000). Recently, it was found that mutations in the dynein heavy chain gene disturb the regular spacing of the syncytial nuclei (Robinson et al, 1999). Nuclear positioning in the interphase syncytium therefore relies on a strict interdependence of microtubule and F-actin localization.…”
Section: Involvement Of Cortical Actin-dependent Structures In Asymmmentioning
confidence: 99%